P38/TF/HIF-α Signaling Pathway Participates in the Progression of CIPN in Mice. (10th July 2019) - Yang, Yang; Hu, Liang; Wang, Chaoyu; Yang, Xing; Song, Ling; Jiang, Chunyi; Li, Yan; Li, Tianxi; Liu, Wen-Tao; Feng, Jifeng
Abstract : Chemotherapy induced peripheral neuropathy (CIPN) is a serious adverse effect of chemotherapeutics with limited pathogenetic mechanism been known. Whether microcirculatory disturbance is involved in CIPN has not been reported. Considering that tissue factor (TF) is an endogenous coagulation factor, we hypothesize CIPN may be induced by the high expression of TF in macrophages and sciatic nerve, which induces the molecular signal related to ischemia and hypoxia. Oxaliplatin (L-OHP) was used to establish CIPN model. Von Frey Hairs was used to measure nociception. The murine macrophage cell line Raw 264.7 was used for cell experiments. Gelatin zymography and western blotting were used to measure the activity or expression of protein. TF expression and MMP-9/2 activity in sciatic nerve and blood are significantly increased by L-OHP. L-OHP increased the release of HSP70 from macrophage and enhanced the expression of p-p38 and HIF-1 α in vivo and in vitro. Hirudin significantly suppressed the overexpression of p38, HIF-1 α and activation of MMP-9/2 induced by L-OHP and attenuated CIPN in mice. This study suggests that a novel HSP70-TLR-4-p38-TF-HIF-1a axis may play a pivotal role in the pathological process of CIPN. It is also shown that the use of anticoagulant Hirudin can inhibit the above mechanisms and improve CIPN.